O diálogo no processo pedagógico para a educação em valores humanos - Santos, Maria Madalena dos (2022)
This study has as its theme Dialogue in the Pedagogical Process for Education in Human Values. It belongs to the line of research related to the educational process and teacher training of the postgraduate program in education at the Catholic University of Brasília (UCB). The general objective is to research the implications of dialogue, in pedagogical practices, for the promotion of an education in human values in the Elementary School of a State Public School. It was used as a theoretical support and to support the research, authors such as Síveres (2015), Tardif e Lessard (2014) Rogers (2009), Moran (2011), Vygotsky (1991), Freire (2003), Bergoglio (2013), Buber (2009) Montessori (2003) among others. The methodology adopted was a qualitative and quantitavive research approach, with methodological procedures of interview and questionnaire. Seven teachers from the 7th, 8th and 9th grades of Elementary School in the public school system participated in the interview and 122 students responded to the questionnaire. Data analysis sought to analyze the perceptions of the teachers and students about dialogue as a welcoming instrument in pedagogical practice for the construction of human values in education, were analyzed based on the studies of Bardin (2016). From the generation of data it was possible to perceive the relevance of dialogue for a consistent pedagogical process in the educational scope, for the realization of education in human values. The teachers were unanimous in recognizing the effectiveness of dialogicity to obtain a mutual exchange in the course of learning, and to build a harmonious interpersonal space with techniques that lead to collectivity, just as the students recognized the practice of dialogue as a paramount factor for learning. However, the need for a representative look at the training of professionals is highlighted, envisioning the strengthening of the team regarding the opening for the practice of knowledge focused on human values.